The Effect Of Position And Workload Analysis On Employee Performance With Service Quality As An Intervening Variable In The Manpower Office Langkat Regency - Sri Wahyuni G. Singa; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
In achieving organizational goals, it requires a variety of resources ranging from human resources, equipment, machinery, finance, and information resources. Human resource management, abbreviated as MSDM, is a science or way of managing the relationship and role of resources (workforce) owned by individuals efficiently and effectively and can be used optimally so that the goals with the company, employees and society are maximized. The results of this study are as follows: Workload has a negative and significant effect on Employee Performance with the original sample value of -0.251 and p values of 0.044. Workload had a negative and significant effect on Service Quality with an original sample value of -0.574 and p values of 0.000. Position has a positive and insignificant effect on Employee Performance with an original sample value of 0.192 and p values of 0.061. The position had a positive and significant effect on Service Quality with an original sample value of 0.366 and p values of 0.005. Service Quality has a positive and significant effect on Employee Performance with an original sample value of 0.532 and p values of 0.000. Workload has a negative and significant effect on Employee Performance through Service Quality with a value of -0.305 and p values of 0.002. Jabtan has a positive and significant effect on Employee Performance through Service Quality with a value of 0.295 and p values of 0.005.